Training on the Preparation of Case Method and PJBL-Based Learning Tools as Strengthening 21st Century Skills - Mahya Dewi, Ucia (Jurnal Pengabdian Masyarakat Bestari, 2024)
This Community Service (PKM) aims   to provide knowledge, experience and skills for prospective teachers in terms of developing learning tools based on the Case            method and PJBL. This training activity consists of three stages, including the preparation, implementation and evaluation stages of the implementation method of training on the preparation of learning tools based on the Case method and PJBL is carried out in two forms, namely the provision of material and practice. Based on   the results of the training on the preparation of learning tools based on Case Method and PJBL for prospective teachers as a strengthening of 21st century skills, it was obtained that prospective   teachers have understood and    compiled            well    how to design, compile, and implement teaching modules and their attachments (LKPD, teaching materials,       assessment, media, and teaching materials) based on the case method and PJBL.